PATHOMORPHOLOGICAL CHANGES IN REGIONAL LYMPH NODES AMONG COVID-19 PATIENTS: CORRELATIONS WITH DISEASE SEVERITY AND CLINICAL OUTCOMES - Raimqulov Rivoj Sobir oʻgʻli (American Journals, 2024)
The COVID-19 pandemic, caused by the SARS-CoV-2 virus, has significantly impacted global health, with severe cases leading to substantial morbidity and mortality. While primarily a respiratory disease, COVID-19 affects multiple organ systems, including the lymphatic system, where pathomorphological changes in regional lymph nodes can indicate disease severity. This study explores the pathomorphological alterations in lymph nodes of COVID-19 patients, analyzing their correlations with clinical outcomes. Findings reveal notable changes such as lymphoid depletion, necrosis, and altered immune cell composition, including reduced CD4+ T cell counts. These alterations were associated with increased disease severity, extended hospital stays, and higher mortality rates. The results suggest that lymph node pathomorphological assessments may serve as valuable biomarkers for predicting disease progression and guiding therapeutic strategies in COVID-19 management. Integrating these evaluations into clinical practice could enhance patient outcomes by identifying individuals at greater risk of severe complications.
Keywords: COVID-19, SARS-CoV-2, pathomorphological changes, regional lymph nodes, lymphoid depletion, necrosis, immune cell composition, disease severity, clinical outcomes, biomarkers.